Abiotic Drivers of Seedling Bank Diversity in Subtropical Forests of Southern China - Martini, Francesco; Zou, Chaobo; Song, Xiaoyang; Goodale, Uromi Manage (Frontiers in Ecology and Evolution, 2021)
Abiotic factors are important to shape plant community composition and diversity through processes described as environmental filtering. Most studies on plant diversity in forests focus on adult trees, while the abiotic drivers of forest seedling community characteristics are less understood. Here, we studied seedling banks’ composition, richness, diversity, and abundance, and investigated their relationships with microsite abiotic conditions along a wide elevational gradient. We sampled seedling communities in 312 1-m2 quadrats, distributed in 13 one-ha plots in four subtropical forests in south China, covering an elevation gradient of 1500 meters, for two years. We measured light availability, slope, and 11 soil nutrients for each seedling quadrat. We used analysis of similarities and multivariate analysis of variance to compare the composition and abiotic drivers of the four forests’ seedling communities. We then used mixed models and structural equation modeling to test the direct and indirect effects of abiotic factors on seedling species richness, diversity, and abundance. The differences in seedling community composition among these forests were mostly explained by differences in elevations and soil nutrients. Seedling diversity as Shannon and Simpson diversity index decreased with increasing elevation and increased with increasing slope, but seedling abundance and species richness did not. Elevation had an indirect effect on Simpson’s diversity index through modulating the direct effects of soil properties. Our findings show that soil properties play a prominent role in favoring differentiation in species composition among the four forests we studied and provide additional evidence to decreasing species diversity with elevation. However, this was reflected in decreasing Shannon and Simpson indices rather than species richness, which is more commonly studied. Whether and to what extent future environmental changes in climate and soil acidification will alter future forest composition and diversity needs to be investigated.